Strategi Penanaman Karakter Islami pada Santri di Asrama SMK Ma’arif 5 Gombong Kebumen - Nasirudin; Munjahid; Samsudin (AN NUR: Jurnal Studi Islam, 2022)
The purpose of this research was to determine the strategy of inculcating Islamic character in students in dormitory of SMK (Vocational High School) Ma'arif 5 Gombong, what character values were there, and the supporting and inhibiting factors in the learning process there. This research was qualitative with data collection through observation, interviews and documentation. The validity of the data was done by using the triangulation method. The study results stated that the strategy of planting Islamic students in dormitory of SMK Ma'arif 5 Gombong was exemplary, disciplined, habituation. While the values of Islamic character were pious, grateful, polite, polite, honest, disciplined, and respecting time. The supporting factors for this strategy were the high level of conditioning, the presence of CCTV, good management, while the inhibiting factor was the diverse input of students and not all students had the intention to study religion.